Kinematic modeling of the technique Stalder backward to handstand on the uneven bars - Petkovic, E. (Facta Universitatis: Series Physical Education and Sport, 2019)
Optimizing the technique of successful performance is important for detecting different technique styles that occur in female gymnasts. The aims of this research were to define an optimal kinematic model of the Stalder backward to handstand on the uneven bars exercise, as well as factors that most greatly affect the successful performance of the selected exercise, performed at the 39th and 40th World Cups in Artistic Gymnastics in Maribor (SLO). The sample of participants consisted of eight female gymnasts who participated in the Finals and performed the above mentioned exercise. Kinematic parameters were determined by the use of the Ariel Performance APAS 3-D video system, and anthropometric 16 reference points with four body segments (foot, center of gravity of the body-CG, shoulder joint and head). CG was calculated based on the model presented by Winter in 2009. The results of the research defined the kinematic exercise model that requires four phases: 1) Upswing from a handstand position to balance the resistance front; 2) Downswing to upswing with clear support; 3) Lower vertical passing; 4) Swing to handstand position. Variability of the trajectory of referent points is necessary as an indication of the successful performance of the Stalder backward to handstand on the uneven bars technique. In the current research, the variability for the successful technique for CG trajectory values decreases from -0.767m to -1.045m, while the trajectory values of the shoulder point decrease from 0.689m to 0.488m under the axis of rotation. The information given could optimize the performance of other young gymnasts at all levels of performance.